2023
DOI: 10.3390/pathogens12030477
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Antimicrobial Peptides from Food Proteins: Perspectives and Challenges for Controlling Foodborne Pathogens

Abstract: Bioactive peptides (BAPs) derived from food proteins have been extensively studied for their health benefits, majorly exploring their potential use as nutraceuticals and functional food components. These peptides possess a range of beneficial properties, including antihypertensive, antioxidant, immunomodulatory, and antibacterial activities, and are naturally present within dietary protein sequences. To release food-grade antimicrobial peptides (AMPs), enzymatic protein hydrolysis or microbial fermentation, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 164 publications
0
3
0
Order By: Relevance
“…Food-derived peptides are a promising strategy to control harmful bacteria, especially those resistant to antibiotics [ 45 ]. Remarkably, antibacterial activity was demonstrated by the chicken hydrolysate and C25 against an antibiotic-resistant bacterium, Proteus vulgaris F24B ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Food-derived peptides are a promising strategy to control harmful bacteria, especially those resistant to antibiotics [ 45 ]. Remarkably, antibacterial activity was demonstrated by the chicken hydrolysate and C25 against an antibiotic-resistant bacterium, Proteus vulgaris F24B ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Food protein-derived peptides have been considered outstanding candidates to alleviate hypertension owing to their excellent physiological regulation activities. 13–15 Another study reported that the collagen peptide Phe-Leu-Ala-Pro (FLAP) could attenuate kidney injury by inhibiting oxidative stress and inflammation in carbon tetrachloride (CCl 4 )-induced mice, probably by influencing the Nrf2/anti-response element (ARE) and PI3K/AKT/NF-κB signaling pathways. 16 Another study demonstrated that marine fish protein peptides (MFPPs) significantly reduce hyperuricemia (HUA)-induced kidney inflammation by down-regulating the levels of inflammatory factors (TNF-α, IL-6, and IL-10) in kidney tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides have been thoroughly researched for their health advantages and possible applications as nutraceuticals and functional food ingredients [ 1 ]. Emerging antibiotic resistance (ABR) related to foodborne illnesses harms both human and animal populations as well as the economy and human health suffers greatly from bacterial resistance which prompts food to deteriorate and causes health problems.…”
Section: Introductionmentioning
confidence: 99%